PRIORITIES OF FINANCE AND CREDIT POLICY - Mikhail N. Sidorov (Вестник Российского экономического университета имени Г. В. Плеханова)
Today managing companies and whole countries is turning into finance management, ideology of cash management of people and countries dominates. The article investigates problems of finance system development and directions of enhancing the Central Bank operations. It is shown that it is necessary to prepare for crisis pressures and sanctions beforehand and to forecast possible consequences. The article analyzes internal and external reasons for the finance crisis and puts forward measures aimed at speeding up economic growth in the country as well as effective foreign economic policy. According to the author we should develop home production of goods and services to balance demand and supply and stabilize prices.